A randomized usability assessment of simulated naloxone administration by community members. (11th September 2018) - Eggleston, William; Podolak, Christine; Sullivan, Ross W.; Pacelli, Lauren; Keenan, Michael; Wojcik, Susan
Abstract: Background and Aims: Expanded access to naloxone has been identified as a key intervention for reducing opioid‐related morbidity and mortality. It is not known which naloxone device will result in rapid, successful administration when administered by community members. The aims of this study were to estimate and compare (1) the rate of successful administration and (2) time to successful administration for single‐step nasal spray, multi‐step atomized nasal spray and intramuscular simulated naloxone by community members. Design: A prospective, single‐site, open‐label, randomized usability assessment of simulated naloxone administration in a convenience sample of community members. Participants were randomized to single‐step nasal spray (SP), multi‐step atomized nasal spray (AT) or intramuscular simulated (IM) naloxone and asked to administer the simulated medication to a mannequin after completing a 2‐minute training video. Setting: New York, USA at a state fair that attracts between 60 000 and 120 000 individuals daily. Participants: A total of 138 participants completed the study over a 2‐day period in September 2016. All participants were at least 18 years of age and had no prior naloxone training. Measurements: The rate of successful administration and time to successful administration were recorded for each device. Findings: The SP device (100%; P < 0.001) had a higher rate of success compared with the IM device (69.6%). Although success differed between the AT (89.1%) device and IM device, as well as the AT device and SP device, these differences were not significant. The SP device also had a shorter median time to successful administration (34.3 sec) compared with the IM (99.9 sec; P < 0.001) and AT (110.3; P < 0.001) devices. Conclusions: After video training, community members are able to (1) administer single‐step nasal spray naloxone with a higher rate of success than intramuscular naloxone in a simulated overdose setting and (2) administer single‐step nasal spray naloxone more rapidly than both intramuscular and multi‐step atomized nasal spray naloxone.